Wangi Jadi Saksi: A Historical Re-reading of the Kinship between Tuah-Jebat: (Teater Wangi Jadi Saksi: Satu Bacaan Semula terhadap Sejarah Setia Kawan Tuah-Jebat) (Malay Literature, 2017)
The story of Hang Tuah and Hang Jebat in the classical texts Sulalat al-Salatin and Hikayat Hang Tuah has been a source of inspiration to filmmakers, theatre directors and songwriters. The first audio-visual film that projected the solidarity of Tuah-Jebat in 1956 was titled Hang Tuah under the direction of Phani Majumbar. This was then followed by the film Hang Jebat directed by Hussein Hanif in 1961. Although these two films were among the earliest adaptations that resurrected the characters of Tuah-Jebat on the big screen, however, it was evident that the films had shown certain inclinations during the filming process. This is inevitable for a film, drama or theatrical adaptation. In an adaptation, differences in reading or interpretation are a normal occurrence; they reflect a director's personal creativity in the adaptation process. U-Wei Haji Saari reminds us of this process by bringing new light to the story of the two legendary figures through his work "Wangi Jadi Saksi". In particular, the work features the character Wangi, who is a witness and a secret keeper to the fight between two friends, touted as legendary in Malay society. This paper aims to explain the concept of adaptation and the relevant interpretation in U-Wei Haji Saari's rereading of the stabbing incident through the character of Wangi guided by an intertextual framework. It argues that U-Wei Saari, in his re-interpretation of the stabbing between Tuah and Jebat, has actually created a new text, which challenges views regarding the relationship between Tuah and Jebat which has been accepted by society for many centuries.Keywords: Hang Tuah, Hang Jebat, U-Wei, adaptation, re-interpretation